Improving moisture distribution pattern of subsurface drip irrigation in sandy soil by using synthetic soil conditioner - Zin El-Abedin, T. K. (2006)
Although, subsurface drip irrigation is controlled system without negative environmental impacts associated with leaching or runoff. However, poor uniformity of moisture content and distribution pattern especially at the upper layer (0-5 cm) in the sandy soil was observed by several studies. Therefore, three stages of the experiments were conducted to improve the uniformity of the moisture content under the subsurface drip irrigation especially in sandy soil. First stage of the experiments were conducted to investigate the effect of the soil texture, sandy (Bostan area) and sandy loam (El-Hamam area) on the soil water content uniformity and distribution pattern. This experiment was conducted on lateral depths (0 and 15 cm for simulation of surface and subsurface drip irrigation systems, respectively) to indicate the difference in water losses and the uniformity of soil moisture distribution as function of soil texture effect and dripper line position. The second stage of the investigation was consternated on the selection process of the appropriate buried depth of the subsurface drip laterals (10 and 15 cm) under different operating pressure (0.5, 1.0 and 1.5 bar). After then, the optimal system was used in presence of synthetic soil conditioner thin layer at different locations at (25 and 30 cm) as a third stage of the experimental procedure. Soils were uniformly packed in a 50 x 50 x 100cm soil box. The dripper line with two emitters was inserted at certain depths. The polyacrylamide polymer was dissolved in the laboratory and diluted to 0.01% as appropriate concentration which was applied in rate 12.3 kg/fed (Aboamera et al., 2000). The polymer was sprayed directly to the soil surface at the desired depths. The results pointed out that the water front was less progressed in sandy loam soil, which caused increasing in the water volume use from each emitter in sandy loam soil by 64 % than that obtained in sandy soil. The studies indicated that subsurface irrigation saved the water consumption by 61 and 39 % for both soil textures the sandy (Bostan) and the sandy loam soil (El-Hamam), respectively, than the surface drip irrigation. The moisture content distribution pattern indicated that the dripper line at 15 cm depth was better than the 10 cm depth under any operating pressure. The average moisture content was 10.6% until soil depth 43 cm for 15cm dripper line depth, while the average of moisture content was 9.4% until soil depth 39 cm for 10cm dripper line depth under operating pressure 1.0 bar without polymer. The synthetic soil conditioner thin layer depth resulted in changing the pattern of the water front spreader and diverted the water cone below and above the dripper line to be moved more horizontally than vertically. Also, it was indicated that the deeper the polymer depth was located, the better the water front distribution was progressed upward and downward. The preferable combination was at dripper line 15 cm depth and polymer layer 30 cm depth working under operating pressure 1.0. However, it should an economical study to indicate the profit due to increasing the yield due to the moisture distribution and the water holding improvement and it would overcome the expenses of baying and manipulation of the synthetic soil conditioner or not.
Includes references.
Summary in Arabic.
1
Keywords: Microirrigation -- Environmental aspects; Sandy soils; Soil moisture; Soil conditioners